Embroidery handbook for beginners : an illustrated guide to tools, techniques + stitches - Guidicelli, Catherine (Schiffer Craft, 2025)
Try embroidery successfully with this clear guide offering all the stitches and techniques with easy-to-follow diagrams and a fun-loving attitude.